Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s00253-022-12029-3
|View full text |Cite|
|
Sign up to set email alerts
|

The roles of DNA methylation on the promotor of the Epstein–Barr virus (EBV) gene and the genome in patients with EBV-associated diseases

Abstract: Epstein–Barr virus (EBV) is an oncogenic virus that is closely associated with several malignant and lymphoproliferative diseases. Studies have shown that the typical characteristic of EBV-associated diseases is aberrant methylation of viral DNA and the host genome. EBV gene methylation helps EBV escape from immune monitoring and persist in host cells. EBV controls viral gene promoter methylation by hijacking host epigenetic machinery to regulate the expression of viral genes. EBV proteins also interact with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 119 publications
(152 reference statements)
0
18
0
Order By: Relevance
“…EBV DNA is unmethylated within the virion, while it becomes methylated when entering infected cells 38 . Among which, an important regulator is the methylation of C‐promoter region 39 . Unmethylation was predominant in most samples from control group (Table S7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBV DNA is unmethylated within the virion, while it becomes methylated when entering infected cells 38 . Among which, an important regulator is the methylation of C‐promoter region 39 . Unmethylation was predominant in most samples from control group (Table S7).…”
Section: Discussionmentioning
confidence: 99%
“…38 Among which, an important regulator is the methylation of C-promoter region. 39 Unmethylation was predominant in most samples from control group (Table S7). It seemed most of the EBV DNA in the samples was probably from free EBV virion.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the CpG-island methylator phenotype (CIMP), EBVaGCs belong to the high (CIMP-H) category ( 129 , 151 ). In fact, over 1000 genes have been found to be differentially methylated by EBV, with hypermethylated genes enriched in Wnt and protein kinase signalling pathways, among other cancer-associated pathways ( 152 154 ). EBV is also noted to express a number of miRNAs, with said miRNAs functioning to inhibit pro-apoptotic genes and promote cell survival, as well as regulate the expression of EBV-associated genes ( 115 , 155 ).…”
Section: Hallmarks Of Cancer In Ebvagcsmentioning
confidence: 99%
“…Another drug currently undergoing clinical trials, zebularine, was previously shown to demethylate the STING promoter, which regulates expression of the cGAS/STING innate immune pathway, resulting in increased CD8+ T and NK infiltration, as well as reduced tumor burden in GC cell line-based models ( 283 ). The benefits of these classes of drugs include the reversibility of effects, due to epigenetic changes, as well the possibility of reversing changes in the TME ( 154 , 284 ). Downsides of such drugs include the potential of non-specific gene activation as a result of demethylation, which may include oncogenes, as well as the lack of studies exploring the long-term effects of epigenetic therapies ( 129 ).…”
Section: Immunotherapy and Other Treatmentsmentioning
confidence: 99%
“…Hypomethylating agents, such as azacytidine (AZA), have the potential to reduce genomic methylation levels and reactivate hypermethylated tumor suppressor genes. Therefore, targeting DNA methylation may represent a novel therapeutic strategy for EBV-associated diseases (Zhang et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%